Relationships between poverty and AIDS Illness in South Africa: an investigation of urban and rural households in KwaZulu-Natal. - Steinert, J; Cluver, L; Melendez-Torres, G; Herrero Romero, R (Taylor and Francis, 2016)
The association between poverty and HIV/AIDS in Sub-Saharan Africa remains contested. A better understanding of the relationship between the prevalence of poverty and the disease is essential for addressing prevention, treatment, and care. The present study interrogates this relationship, using a cross-sectional survey of 2477 households in urban and rural KwaZulu-Natal, South Africa. Structural equation modelling was employed to estimate the correlations between poverty and AIDS illness. The analysis revealed a correlation of rpb = 0.23, denoting that a higher level of household poverty was associated with a higher likelihood of being AIDS-unwell. Post hoc t-test showed that receipt of a disability grant by AIDS-affected households was associated with significantly lower poverty, compared to AIDS-affected households not receiving the grant, t(654) = 3.67, p < .01. Geographic location was found to confound the correlation: the strength of the relationship between poverty and AIDS was decreased to rpb = 0.15 (p < .001) for the urban and rpb = 0.16 (p < .001) for the rural sub-population. Findings suggest the importance of two sets of policies: those that address the potential upstream risk of poverty through economic interventions, and those that alleviate the impoverishing effects of AIDS illness for affected households.